2019
DOI: 10.1111/plb.12975
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and growth of Fagus sylvatica and Quercus robur seedlings in response to temperature variation in the parental versus offspring generation

Abstract: Plants are known to respond to warming temperatures. Few studies, however, have included the temperature experienced by the parent plant in the experimental design, in spite of the importance of this factor for population dynamics.• We investigated the phenological and growth responses of seedlings of two key temperate tree species (Fagus sylvatica and Quercus robur) to spatiotemporal temperature variation during the reproductive period (parental generation) and experimental warming of the offspring. To this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…An asterisk (*) indicates results were confirmed using a Log-Likelihood Ratio Test (see Methods). consistent with a number of other studies that have shown increased temperature of origin is associated with earlier bud burst (Alberto et al 2011;Sampaio et al 2016;Dewan et al 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An asterisk (*) indicates results were confirmed using a Log-Likelihood Ratio Test (see Methods). consistent with a number of other studies that have shown increased temperature of origin is associated with earlier bud burst (Alberto et al 2011;Sampaio et al 2016;Dewan et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Koenig et al (2021, this issue) examined bud burst date in Valley Oak over a 30-yr period, and found that warmer temperatures were associated with earlier bud burst. Studies that used artificial warming to examine the impact of increased temperatures on phenology have found that warmer temperatures are associated with earlier leafing out dates (Morin et al 2010;Fu et al 2013;Fu et al 2016;Dewan et al 2020;Faticov et al 2020). Thus, in addition to the genetic basis of bud burst timing, the environment can influence when leaves emerge.…”
Section: Sitementioning
confidence: 99%
“…in Slovenia recorded an increasing trend of earlier onset by 1.52 days per 10 years, while no changes were observed in lower elevations ( Čufar et al., 2012 ). Dewan et al. (2020) highlight the spatiotemporal fluctuations of spring air temperature due to ongoing climate change, resulting in a rapid phenological response in beech.…”
Section: Discussionmentioning
confidence: 99%
“…However, climate change is also expected to affect the richness, diversity and community composition of microbial communities associated with plants [7,41,48]. Additionally, the majority of studies about the effects of climate change on the plant microbiome have focused on annual crops [56, 70,75], whereas less studies have focused on trees, despite their invaluable importance for global ecosystem functioning [8, 23,29]. While we have a good understanding of the effect of warming and drought on the plant physiology and tness, we lack insights into the independent and interactive effects of warming and drought on the plant-associated microbiome.…”
Section: Introductionmentioning
confidence: 99%